Psychological well being, Stress at Work and Safety Behaviour at Sea of Seafarer on Shipping Company - G Nurcholis; M Qurniawati (Technium Social Sciences Journal, 2020)
In the shipping industry, safety is the main concern for the management of the shipping industry organization. Several studies have shown that one of the causes of ship accident at sea is caused by human error, in this case unsafe behaviour carried out by seafarer. Research studies have shown that one of the factor of accident at sea is caused by human error, which means unsafe behaviour carried out by seafarer. The work environtmental at the sea that are full of risk, and vulnerable to work stress, can cause unsafe behaviour. Related to it, seafearer who have good psychological well being, and can manage the stress of work experienced well, can improve safety behaviour. This study aims to determine the effect of psychological well being, work stress on safety behaviour at sea on seafarers of shipping companies in Indonesia. This research uses a quantitative approach. Data collection was carried out through a survey of 107 seafarers of PT. Pelni Surabaya. Sampling techniques uses incidental sampling. Analysis of research data was conducted using multiple linear regression analysis. The result showed that there was an influence between psychological well being, work stress on safety behaviour partially or simultaneously. Safety behaviour at sea can be seen from safety participation and safety compliance, where it can be improved if psychological well being is good and work stress experienced by seafarers can be a motivator to carry out safety behaviour. The result of this study also indicate that researchers advice to shipping companies is to create effective programs to improve psychological well being of seafarers and releave work stress to improve safety behaviour at sea.